Le documentaire cubain entre nostalgie et désillusion, Le Rideau de sucre de Camila Guzmán - Magali Kabous (Caravelle)
Documentary has always occupied a very important place in the Cuban cinematographic production since 1959. Camila Guzmán was born in Chile and was raised in Cuba after her parents’ exile. Later, when she became an adult, she shot a documentary, Le Rideau de sucre (The sugar curtain), aiming to look back on her Cuban childhood by personally bearing witness and questioning her old classmates. Through different life journeys, exiles’ speeches and others belonging to the ones who remained in the island, she draws a balanced picture of Cuban reality in the 2000s.